Pengaruh Kombinasi Teknik Relaksasi Benson dan Terapi Quranic Healing terhadap Tingkat Nyeri pada Pasien Kanker yang Menjalani Kemoterapi - Noor Aini; Indah Sri Wahyuningsih; Mohammad Arifin Noor (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Pain is one of the main problems that cancer patients who undergo chemotherapy often experience, both as a direct result of the development of the disease and as a side effect of the therapy undergone. Pain that is not handled properly can decrease the quality of life, interfere with daily activities, and negatively impact the patient's psychological state. Therefore, non-pharmacological interventions are important as a companion effort to medical treatment. This study aims to analyze the effect of the combination of Benson relaxation technique and Quranic Healing therapy on the pain level of cancer patients undergoing chemotherapy at the Sultan Agung Islamic Hospital Semarang. The research uses a quasi experiment design with a nonequivalent control group design approach. The sample size was 36 respondents, divided into intervention groups and control groups, each consisting of 18 respondents. Pain levels were measured with the Numeric Rating Scale (NRS) instrument before and after the intervention. Data analysis was performed using the Wilcoxon test for differences within groups and the Mann–Whitney test for differences between groups. The results showed a significant decrease in pain levels in the intervention group (p = 0.000) compared to the control group (p = 0.046), with a significant difference between the two groups after the intervention (p = 0.001). In conclusion, the combination of Benson relaxation techniques and Quranic Healing has been shown to be effective in reducing pain in cancer patients undergoing chemotherapy. These interventions can be recommended as an alternative to non-pharmacological nursing measures to improve the comfort and quality of life of cancer patients.